The Effect of Fungus on Concrete as Self-Healing Agent: A Systematic Review - DOM, Aliah; Juki, Irwan (Recent Trends in Civil Engineering and Built Environment, 2022)
Concrete is made from combination of three basic materials which is fine aggregate, cement and water. Concrete is widely used around the world due to economical and easy to cast into shape. Due to moisture expansion, concrete has a high tendency to crack easily. The effect of crack on concrete lead to a reduction in the lifespan of the concrete. In this study, self-healing concrete is introduced to fill up the crack. Fungi is a new biological approach that has added into concrete to produce calcium carbonate. Although fungi have ability to be a self-healing agent and promote precipitate of CaCO₃ but the study about this topic is still in early stage. The main objective of this study is to investigate the effect of fungus as a self-healing agent on concrete and to identify the most factors effect self-healing in bio-concrete using fungus through case study. In this study, the systematic review used to evaluate the effect of fungus in concrete structure as self-healing agent. It undergoes a few process to get the suitable article to used for this study. From previous study, the method used is X-Ray Diffraction (XRD) and Scanning Electron Microscopy (SEM) to confirmed that fungi have ability to precipitate calcium carbonate. From this study, it helps to identify the effect of fungus on concrete as self-healing agent.